PEMBERIAN LATIHAN VIRTUAL REALITY LEBIH BAIK DARIPADA LATIHAN KONVENSIONAL TERHADAP PENINGKATAN FUNGSIONAL TANGAN PADA PASIEN PASCA STROKE - Nuryanto, Muhammad Ruslan; Purwa Samatra, DW.Pt.Gde; Irfan, M.; Dinata, I Made Krisna; Sagung Sawitri, Anak Agung; -, Sugijanto (Sport and Fitness Journal; Volume 7, No.1, Januari 2019DO - 10.24843/spj.2019.v07.i01.p10, 2019)
ABSTRACT Background: Stroke is a problem of neurologist brain who causes occurrence of neurologist deficit such as a weakness of upper extremity. For instance, limited of hand functional and movement because of abnormality tonus that occur instability muscle. Methods: The purpose of this research was to knew effect of additional virtual reality exercise better than conventional exercise to enhancement of functional hand for Stroke patience. This research is experimental study which used a Randomize Control pre-post test design. The first category is 6 samples be given Virtual reality Exercise with Sensor Leap Motion Controller during 30 minutes. And the second category is 6 samples be given conventional exercise during 30 minutes. The times of research for 4 weeks under the supervision of Physiotherapist to do well. Measurement test of hand functional with used of Wolf Motor Function Test instrument. Results: The result of this research showed to the first category occur of ability improvement of hand in the amount of 14,21% and be obtained value p=0,027, which one p<0,05. The second category occur of ability improvement of hand in the amount of 8.47% and be obtained value p=0,001, which one p<0,025. Meanwhile, the different of ability improvement of hand on both categories showed there is a significant different (value p=0,007, which is p=<0,005). The conclusion of this result that Virtual reality Exercise with Sensor Leap Motion Controller better than conventional exercise to enhancement of functional hand for Stroke patience. Keywords: Stroke, ability of hand functional, Exercise of Virtual reality, Conventional exercise, Wolf Motor Function Test.